2022
DOI: 10.1101/2022.04.04.487059
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In Utero Activation of NK Cells in Congenital CMV Infection

Abstract: Background: Congenital cytomegalovirus (CMV) infection is the most common infectious cause of birth defects and neurological damage in newborns. Despite a well-established role for NK cells in control of CMV infection in older children and adults, it remains unknown whether fetal NK cells can sense and respond to CMV infection acquired in utero. Methods: Here, we investigate the impact of congenital CMV infection on the neonatal NK cell repertoire by assessing the frequency, phenotype, and functional profile o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Nevertheless, cord blood sera ADCC responses were strongly associated with protection against transmission and anti-UL16 IgG was highly transferred to uninfected infants. Vaaben et al also recently observed that cord blood NK cells expressing FcγRIII/CD16 are expanded in utero following cCMV infection (45,46). Taken together, these studies suggest that maternal ADCC-activating antibodies transferred across the placenta and fetal NK cells expressing FcγRIII may synergize to defend against HCMV (45,46).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Nevertheless, cord blood sera ADCC responses were strongly associated with protection against transmission and anti-UL16 IgG was highly transferred to uninfected infants. Vaaben et al also recently observed that cord blood NK cells expressing FcγRIII/CD16 are expanded in utero following cCMV infection (45,46). Taken together, these studies suggest that maternal ADCC-activating antibodies transferred across the placenta and fetal NK cells expressing FcγRIII may synergize to defend against HCMV (45,46).…”
Section: Discussionmentioning
confidence: 78%
“…Vaaben et al also recently observed that cord blood NK cells expressing FcγRIII/CD16 are expanded in utero following cCMV infection (45,46). Taken together, these studies suggest that maternal ADCC-activating antibodies transferred across the placenta and fetal NK cells expressing FcγRIII may synergize to defend against HCMV (45,46). Therefore, strategies to enhance placental transfer of these potentially protective antibodies through Fc-engineering and to engage fetal and/or neonatal innate immune cells in Fc-mediated immunity should be explored.…”
Section: Discussionmentioning
confidence: 91%